EFFECT OF SCANDIUM ADDITION ON MICROSTRUCTURE, MECHANICAL PROPERTIES, AND ANNEALING BEHAVIOR OF AL-ZN-MG ALLOYS. - Pariz Maulana, Hafid
Aluminum series 7xxx is widely used in the aerospace industry due to its high specific strength and specific stiffness. The development of mechanical properties and thermal stability of Al-Zn-Mg alloy continue to be carried out. The addition of scandium is one method for improving strength, which can produce grain size refinement. The addition of scandium at 0.25 wt% and 0.5 wt% was evaluated in this study to determine how it affected the microstructure, mechanical properties, and annealing behavior of Al-Zn-Mg alloys. The characterizations carried out included metallography, tensile test, Vickers hardness test, Scanning Electron Microscopy-Energy Dispersive Spectroscopy (SEM-EDS), and X-ray Diffraction (XRD). The results showed that the addition of scandium at 0.25 wt% and 0.5 wt% could result in a decrease grain size of 22 ?m (31%) and 55 ?m (79%) in cast condition, 37 ?m (54%) and 45 ?m (65%) in homogenized condition, increased hardness by 10 HV (8%) and 3 HV (2%) in cast condition, can inhibit recrystallization and grain growth. Meanwhile, only the addition of scandium at 0.5 wt% can increase the strength by 147 MPa (70%) in the as cast condition and 94 MPa (29.6 wt%) in the homogenized condition.